MORPHOLOGY, DISTRIBUTION, AND SIGNIFICANCE OF SPECIES OF THE GENUS NONEA MEDIK. IN THE KASHKADARYA REGION (World Bulletin of Public Health, 2025)
This study examines the morphology, distribution, and ecological significance of species belonging to the genus Nonea Medik. in the Kashkadarya region. The research analyzes their structural characteristics, habitat preferences, and potential applications in medicine and agriculture. The findings contribute to a better understanding of the biodiversity of the region and the role of these species in local ecosystems. The genus Nonea Medik. plays an important role in the ecosystems of the Kashkadarya region, contributing to biodiversity, soil stabilization, and medicinal plant resources. Their morphological adaptations allow them to thrive in harsh environments, making them valuable subjects for ecological and pharmacological studies. Further research and conservation efforts are necessary to ensure the sustainable use and protection of these species in Uzbekistan.
Keywords: Nonea Medik; morphology; distribution